Effect of portal vein embolization on treatment plan prior to major hepatectomy for hepatocellular carcinoma. Issue 8 (August 2019) - Loveday, Benjamin P.T.; Jaberi, Arash; Moulton, Carol-Anne; Wei, Alice C.; Gallinger, Steven; Beecroft, Robert; Fischer, Sandra; Ghanekar, Anand; McGilvray, Ian; Sapisochin, Gonazolo; Greig, Paul D.; Tan, Kongteng; et al.
Abstract: Background: Portal vein embolization (PVE) is used before major hepatectomy for hepatocellular carcinoma (HCC) to increase future liver remnant (FLR) volume. However, this may increase tumour growth rate, leading to more extensive resections. This study aimed to determine the effect of tumour growth, following PVE, on treatment plan. Method: Retrospective cohort study conducted on patients treated from 2008 to 2015 with PVE before major hepatectomy for HCC. Liver and tumour volumetry was performed on pre- and post-PVE CT scans. Image-based and actioned plans were compared before and after PVE. Results: Thirty-one patients received PVE. Non-tumour total liver volume decreased (median 1440 to 1394 cm 3 ; p = 0.031), while tumour (median 161–240 cm 3 ; p < 0.001) and FLR volumes (median 430–574 cm 3 ; p < 0.001) increased. The treatment plan changed in 15/31 patients: more extensive resection (n = 6), less extensive resection (n = 1), no resection as scheduled (n = 8). Tumour progression accounted for a clinically relevant change in treatment plan in 8/31 patients. Conclusion: Following PVE in the setting of HCC, tumour progression accounts for a change in treatment plan in approximately a quarter of patients. Further research is warranted to determine whether additional liver directed therapy should routinely be used to slow the growth of HCC post-PVE.